Visual enhancement algorithm of 3D virtual interactive multimedia images. (17th February 2018) - Zhao, Mengde; Chen, Yimin
Abstract: Conventional image methods cannot effectively make image enhancement, there is a poor image quality problems. In this paper, a Retinex image enhancement algorithm based on CLAHE is proposed. The non-local mean denoising algorithm based on Mahalanobis distance is used to denoise the image, and the feature is extracted from the denoised image. By using Retinex enhancement algorithm based on CLAHE, the virtual interactive image vision is enhanced, which can improve the edge details of images and the quality of visual images. Experimental results show that the proposed algorithm can effectively improve the visual quality of the image.